Effects of biofeedback on obstructive defecation--reconditioning of the defecation reflex? - Papachrysostomou, M (1994)
Twenty two patients with obstructive defecation were recruited for relaxation training by domiciliary self regulatory biofeedback. Each patient served as his or her own control for anorectal and proctographic assessments. Biofeedback training improved the obstructive symptoms of the patients and showed significant change in various parameters related to the obstructive defecation syndrome. As examined by isotope dynamic proctography: the defecation rate (% of evacuation/defecation time) was significantly increased (p < 0.05), the anorectal angles at rest and during attempted defecation were made more obtuse (p < 0.05), and the pelvic floor movements were made more dynamic on voluntary contraction of the anal sphincter (p < 0.03). The external anal sphincter electromyographic voltage recorded during defecation was significantly reduced (p < 0.0005) as was the surface anal plug electromyographic electrode voltage (p < 0.0001), which was associated with a greatly reduced anismus index (p < 0.0001). The rectal sensation was improved (p < 0.05), concomitantly. Biofeedback thus improves the defecation act in patients suffering from inappropriate contraction of the pelvic floor and sphincter musculature. Furthermore, this study has shown that biofeedback objectively influences the defecation reflex leading to an improved quality of higher control of bowel function.